Microdynamics Simulation - Bons, Paul.; Koehn, Daniel; Jessell, Mark W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This volume deals with the simulation of metamorphic and tectonic microstrucutres in rocks with a special emphasis on the modelling package "Elle". The first part provides a review of the problems and opportunities in the modelling of microstructures, followed by an introduction to various numerical modelling techniques. In the second part examples of the modelling of  different processes which alter rock microstructure are presented, beginning with individual processes and progressing to modelling multiple coupled processes.
Numerical methods -- Microprocess Simulations -- Case studies and coupling of processes.
Keywords: Earth sciences; Geotechnical engineering; Geology; Earth Sciences, general; Geotechnical Engineering & Applied Earth Sciences; Geology